Cittadinanza formale e cittadinanza dal basso. Un rapporto dinamico - Ambrosini, Maurizio (SocietàMutamentoPolitica, 2016)
The permanent settlement of immigrants of foreign origin, and then the formation of the second and third generations, has long contributed to re-launching the debate on the content and limits of the institution of citizenship, bringing into question the close connection with the national states. The increasing number and the growing diversity of the legal status of foreigners residing in the territory of sovereign states blurs the dividing lines between insiders and outsiders. Therefore this raises questions about the criteria and ways of participation of residents in the community of citizens, with all the obligations and benefits that derive from it. After having considered the citizenship ‘from above’, that is in terms of the type of rights granted to foreign residents, their extent, timing and modes of access, the article presents a more recent branch of studies that starts ‘from below’, i.e. from the point of view of actual practices to access and use, re-interpretations and negotiations of the contents of citizenship: processes in which migrants and refugees take active roles at various levels and in different ways, both individual and collective.